Informe de precios de ganados y carnes de la Patagonia [Marzo 2025] - Tejeda, Edgardo Oscar; Claps, Leonardo; Marciani, Santiago Nicolas; Podgornik, Gabriel; Retamal, Katherina Antonella; Li, Sebastian; La Torraca, Andres Juan; Bain, Ingrid; Pena, Sergio Osvaldo; Schorr, Alan Geoffrey (Centro Regional Patagonia Norte y Centro Regional Patagonia Sur, INTA, 2025)
EEA Chubut